Pengaruh Motivasi dan Disiplin Terhadap Kinerja Guru Disekolah Islam Terpadu Al -Lauzah - Adellya Nanda Ariani; Putri Agustina; Topaz Baida (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
Motivation is a change from within a person that begins with encouragement from someone, this encouragement is preceded by someone's encouragement to achieve certain goals. Discipline also in the teacher's work is the obedience or obedience of educators in carrying out the rules that have been provided with full awareness within themselves which can affect the teacher's performance, it can be seen from the results of the teacher's work by showing the quality or quantity achieved by the teacher. In carrying out this research, it aims to be able to determine the effect of motivation and discipline on teacher performance at the Al-Lauzah Integrated Islamic School either partially or simultaneously. using data analysis techniques, the analysis used is statistical analysis with classical assumption testing, hypothesis t test, hypothesis test f, test the coefficient of determination to find out that each variable influences each other or not at all